Evaluasi Keberhasilan Implementasi Sistem Informasi Manajemen Proyek dalam Meningkatkan Efektivitas Tim Kerja: Evaluating the Success of Project Management Information System Implementation to Enhance Work Team Effectiveness - Rakhmansyah, Mohamad; Sunarjo, Richard Andre; Lutfiani, Ninda; Riskhandini, Dinda Putri; Shepard, Anjani (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
This research aims to evaluate the success of the implementation of the Project Management Information System (SIMP) in increasing the effectiveness of work teams, by utilizing key performance indicators (KPI) as a measuring tool. In the era of digitalization, the use of SIMP is increasingly widespread in various organizations to manage projects and optimize team collaboration. However, although many companies adopt SIMP, implementation results often vary, depending on the effectiveness of using the system in daily practice. The approach used in this research is quantitative descriptive, with data collection through questionnaire surveys to team members who have actively used SIMP in their work for a minimum of six months. Some of the main performance indicators evaluated include time efficiency, quality of work results, team satisfaction, and effectiveness of communication between team members. Data analysis was carried out descriptively to assess the performance of each indicator and identify roles SIMP in supporting overall team performance. The research results show that SIMP plays a significant role in increasing the efficiency of task completion times, improving the quality of project results by reducing errors, increasing team member satisfaction with better collaboration, and facilitating more effective communication between members. Based on these results, it is concluded that SIMP implementation is able to support the effectiveness of the work team as a whole, although there are challenges such as the need for initial adaptation and training. Recommendations are given that companies carry out regular training and system maintenance to ensure the continued effectiveness of SIMP use. It is hoped that this research will provide guidance for other organizations in evaluating and optimizing use SIMP at their workplace.